Association between body roundness index and metabolic syndrome in middle-aged and older adults: a prospective cohort study in China - Haiwei Li; Jing Zhang; Huifang Wang; Liang Luo (Frontiers in Public Health, 2025)
BackgroundThe Body Roundness Index (BRI), an emerging anthropometric parameter calculated from height and waist circumference ratios, currently lacks substantive evidence delineating its etiological connections with metabolic syndrome (MetS) development. Its predictive utility for MetS and clinical applicability remain poorly understood. This study aimed to investigate the association between BRI and the risk of MetS in middle-aged and older adults in China, using both cross-sectional and prospective cohort analyses. We hypothesized that higher BRI is associated with an increased risk of MetS.MethodsThe cross-sectional analysis utilized data from the China Health and Retirement Longitudinal Study (CHARLS), comprising 9,398 participants, while the longitudinal analysis was based on a prospective cohort of 5,934 individuals from the same study, followed over a 4-year period. The BRI was calculated using height and waist circumference. Logistic regression and Cox proportional hazards regression models were employed to evaluate associations between BRI and MetS. To ensure the robustness of the findings, restricted cubic spline plots, subgroup analyses, and sensitivity analyses were conducted.ResultsAfter adjusting for covariates (including age, gender, education, smoking status, drinking status, etc.), cross-sectional analyses revealed that participants in the medium BRI tertile (OR = 4.99, 95% CI: 3.07–8.11) and the high BRI tertile (OR = 13.66, 95% CI: 8.57–21.79) had a significantly higher risk of MetS compared to the low BRI reference group (p < 0.001). Longitudinal analyses demonstrated that the medium BRI group had a 2.71-fold increased risk of MetS (HR = 2.71, 95% CI: 2.29–3.21, p < 0.001), while the high BRI group exhibited a 4.64-fold increased risk (HR = 4.64, 95% CI: 3.94–5.47, p < 0.001) relative to the low BRI group. Restricted cubic spline analyses indicated a nonlinear dose–response relationship between BRI and MetS risk (P for nonlinearity < 0.001).ConclusionElevated BRI is significantly associated with an increased risk of MetS in middle-aged and older adults. Therefore, prospective cohort studies employing longitudinal designs and intervention assessments are needed to determine whether BRI can serve as a modifiable risk marker for MetS.